Efficacy of extracorporeal shock wave lithotripsy for post-transplant kidney stones. Hope or Disappointment? - S. V. Popov; R. G. Huseynov; I. A. Miloserdov; Yu. V. Kisil; D. A. Saydulaev; S. V. Sadovnikov; K. V. Sivak; N. S. Bunenkov; V. V. Perepelitsa; T. A. Lelyavina (Вестник трансплантологии и искусственных органов)
Nephrolithiasis in a transplanted kidney is an important medical and social problem. The presence of renal calculi may not manifest clinically for a long time due to the peculiarities of the surgical intervention during organ transplantation. Development of chronic urinary tract infection and deterioration of the functional ability of the renal transplant in the presence of kidney stones can lead to graft death, which is an immediate threat to the patient’s life. Existing Russian guidelines on the treatment of urolithiasis currently lack a clear strategy for the management of kidney transplant recipients.Objective: to systematize literature data on analysis of the outcomes of extracorporeal shock wave lithotripsy (ESWL) and other methods in patients with post-transplant kidney stones.Results. Thirty-five publications on the research topic were selected. We summarized the information on various therapy options for patients with stones in transplanted kidney: endourological approach, ESWL, percutaneous nephrolithotripsy (PCNL), open surgical treatment (nephrostomy, pyelolithotomy). A modern foreign algorithm for the management of patients with post-transplant kidney stones depending on the severity of obstruction with sepsis and the size of the renal calculi is presented.Conclusion. 1. The presence of stones in a kidney graft is a clinical situation that requires surgical treatment. 2. In clinical practice, different methods of treatment can be used, such as open intervention, ESWL, PCNL, retrograde transurethral manipulations. 3. In most cases, patient management tactics depend on the clinical picture (presence/absence of obstruction) and the size of the calculi. 4. The use of ESWL, as the most frequently used method, testifies to its efficiency and low-traumatic effect.